Mapping Landslide Susceptibility Along the Nandi Escarpment in Malava Sub-County Kakamega County, Kenya - Chepkosgei, E.; Ucakuwun, E. K.; Nduru, G. M. (Africa Environmental Review Journal, 2022)
Landslides may occur in hilly terrain due to a combination of factors like deforestation, heavy precipitation, slope steepness and gravity, land use and cover. Whenever they occur, they may result in disasters such as loss of property and/or life. The frequency of landslidesin any area may be high if all the factors that trigger them are prevalent. The main objective of this study was to determine the factors that influence the occurrence of slope failure over space and time and produce a landslide susceptibility map of the Nandi Escarpment in Kabras area of Malava Sub- County. It also presents the capability of a Remote Sensing and GIS based approach to mapping the susceptibility of hilly terrains, with the Nandi escarpment as a case, to slope failure. A slope failure susceptibility map was used to help in identifying strategic points and geographically critical zones that are prone to landslide risks. The study involved generation of landuse/ landcover maps extracted from Satellite Images, which were taken in the years 1973, 1995 and 2006. SRTM DEM 90 m was used in generating slope and contour maps of the area. Soil maps were obtained as secondary data from Moi University Soil Laboratory and Soil Survey of Kenya, while rainfall maps were obtained from the Kenya Meteorological Department (KMD), Kakamega County. A slope failure risk map of Kabras region was produced by overlaying all thematic maps and analysis using GIS was conducted after assigning appropriate ranks and weights to respective variables. Focused groups discussions were used in data collection and probing historical information on land use changes in the area. The result is a map showing zones with varying degrees of susceptibility to slope failure and slopes steeper than 54o was more susceptible to slope failures. It is opined that such a map will enable decision and policy makers to identify and implement suitable mitigation measures, with hopes of forestalling future losses in life and property in the area of study. Settlement should be limited to slopes of less than 24o since, according to this study, slopes higher than this are prone to sliding. There is need for Kenya ministry of lands and physical planning to ensure sustainable land use activities are conducted in the slopes of various degrees.